An optimised HS-SPME-GC-MS method for the detection of volatile nitrosamines in meat samples. Issue 3 (4th March 2019) - Roasa, Joy; Liu, Huaizhi; Shao, Suqin
ABSTRACT: A method to detect volatile nitrosamines in meat samples was developed using headspace sampling by solid-phase microextraction (HS-SPME), with analysis by GC-MS. A 50/30 µm divinylbenzene/carboxen/polydimethylsiloxane fused silica fibre was selected to extract a total of nine volatile nitrosamines: N-nitrosodimethylamine, N-nitrosomethylethylamine, N-nitrosodiethylamine, N-nitrosodi-n-propylamine, N-nitrosomorpholine, N-nitrosopyrrolidine, N-nitrosopiperidine, N-nitrosodi-n-butylamine, and N-nitrosodiphenylamine. Extraction at 65°C for 45 min with 36% (w/v) NaCl were the optimal conditions determined for the extraction of nine nitrosamines. Excellent linearity was obtained for all analytes with determination coefficients greater than 0.997. Recovery rates were between 92 and 113%. The relative standard deviation ranged from 0.81 to 8.0% for six of the nine compounds, and from 16 to 32% for the other three. For seven out of nine nitrosamines, limits of detection were below 3.6 µg kg −1 and the limits of quantification were below 12 µg kg −1 . The nitrosamine levels in four varieties of processed meat products were investigated to assess the applicability of the method. Based on the results, the developed HS-SPME-GC-MS method proved to be a simple and efficient technique to detect seven out of nine nitrosamines in meat products with adequate sensitivity, accuracy and precision.